Student perspectives of equity, diversity, and inclusion in the curriculum of a UK medical school—A mixed-methods study - Amirmohammad Heidari; Shravani Joshi; Mohamed H. Ahmed; Ibrahim Mahmoud; Jacqueline O’Dowd; Joanne Selway; Oladipo Phillips; Mohamed H. Taha (Journal of Education and Health Promotion)
BACKGROUND: Equity, inclusion, and diversity in medical education are increasingly recognized as crucial for enhancing student engagement and improving health outcomes. This paper aims to analyze trends and assess student attitudes toward ethnic equity, inclusion, and diversity within campus-based modules at the University of Buckingham Medical School, UK. MATERIALS AND METHODS: A mixed-methods approach was employed, involving 97 medical students aged 18–24 years (86.6%) between 2021 and 2023. Quantitative data were gathered through a pretested questionnaire using a five-point Likert scale and analyzed using SPSS software (version 26). Qualitative insights were obtained from five focus group sessions with randomly selected medical students and analyzed thematically. RESULTS: The findings of this study indicated a significant proportion of Asian descent students (56.7%). First-year and White ethnicity students perceived the curriculum as more representative compared to second-year counterparts and peers from other ethnic backgrounds. Notably, first-year students showed a heightened understanding of social science terms, especially “ethnicity,” and 67% of female students demonstrated a deeper comprehension of sociocultural factors influencing health behaviors. Across demographics, there was consistent recognition of these factors impacting patient care. Qualitative findings underscored the importance of representation in medical education, biases in recruitment, and advocated for greater faculty diversity. Additionally, there is a need for a curriculum reflecting diverse dietary habits and including role models from various ethnic backgrounds. CONCLUSION: This study emphasizes the critical need for curricular reform in medical education to prepare students for a multicultural society. Addressing disparities in curriculum representation and promoting diversity within faculties are essential for equipping future healthcare professionals with the skills to provide culturally competent care and navigate diverse patient populations effectively.